"Do Not Believe Every Spirit": Discerning the Ethics of Prophetic Agency in Early Christian Culture. (January 2021) - Tibbs, Eugene C.
Abstract: In early Christian culture, prophets went into ecstasies while having visions and speaking by means of a spirit (enthusiasm). With the waning of prophetic activity in the second century, enthusiasm was not seen in many communal gatherings. When enthusiasm reemerged in Montanism during the late second century, church leaders claimed that speaking in ecstasy never existed as true prophecy in early Christian culture. They argued that true prophets always prophesied with a sound mind. The ecstasy of Montanism exhibited an unsound mind and looked like demonic possession; thus, Montanist prophecy was rejected as false. This paper theorizes that enthusiasm's absence contributed to the critics of Montanist ecstasy who were not used to enthusiasm and therefore did not recognize it as an early Christian practice.